Ethnic Mosaic: Analysis of Management and Productivity of Lowland Rice In South Bangka Regency - Rostiar Sitorus; Iskandar Zulkarnain; Winda Wahyuni (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study investigates the relationship between ethnic diversity and the management practices and productivity of lowland rice farming in South Bangka Regency. The region's multi-ethnic composition—comprising Malay, Javanese, Bugis, and other ethnic groups—offers a unique context to explore how cultural backgrounds influence agricultural decisions and outcomes. Using a mixed-methods approach involving field surveys, in-depth interviews, and productivity data analysis, the study identifies key differences in land preparation, input usage, labor organization, and post-harvest handling across ethnic groups. The findings reveal that ethnic-based variations in farming knowledge and social capital significantly affect productivity levels. The study concludes by recommending culturally tailored agricultural extension strategies to improve rice productivity in ethnically diverse communities.